Pembelajaran Connecting, Organizing, Reflecting, Extending (CORE) Untuk Meningkatkan Kemampuan Berpikir Kritis Matematis Ditinjau dari Self-Efficacy - Aprilia, Indah Silvana; Saputri, Veni (Indo-MathEdu Intellectuals Journal, 2023)
This research aims (1) to see the increase in students' mathematical critical thinking abilities using the connecting, organizing, reflecting, and extending (CORE) learning model in terms of the level of self-efficacy, (2) to find out whether there are differences in the increase in mathematical critical thinking abilities between students who have high and low levels of self-efficacy, and (3) to determine the interaction between the CORE learning model and self-efficacy in improving critical thinking skills. This research used a sample of 57 students from class VII SMP Taruna Terpadu Bogor. The sampling technique for this research uses a cluster random sampling technique. The instruments used are test instruments in the form of critical thinking ability questions and non-test instruments in the form of self-efficacy questionnaires. The results of this research show that (1) there is no difference in the increase in mathematical critical thinking abilities between students who study the CORE learning model and the conventional learning model, (2) there is a difference in the increase in students' mathematical critical thinking abilities between students who have a high level of self-efficacy and low, (3) there is no interaction between the CORE learning model and self-efficacy on mathematical critical thinking skills